PROBABILISTIC SEISMIC HAZARD ASSESSMENT FOR THE TRANH RIVER HYDROPOWER PLANT NO2 SITE, QUANG NAM PROVINCE - Phuong*, Nguyen Hong; Truyen, Pham The; Nam, Nguyen Ta (Vietnam Journal of Earth Sciences, 2016)
In this paper, the results of probabilistic seismic hazard assessment (PSHA) for the Tranh river hydropower plant No2 site, Quang Nam province, are presented. A regional earthquake catalog updated until 2014 and most recent data on active faulting in the area with a radial extent of 100 km from the HPP site were used. Applied modern techniques in the PSHA methodology including logic tree and hazard disaggregation allow to adopt different models of seismicity, seismic sources and ground motions for the study area. A set of the probabilistic seismic hazard maps showing distribution of the median peak ground acceleration (PGA) and intensity I (according to the MSK-64 scale) predicted for the periods of approximately 200, 500, 1000 and 10.000 years, respectively was compiled for the region. For the HPP site, the calculated hazard is presented in terms of the hazard curves and the seismic hazard disaggregation graphics at the site. For the 500 year period, maximum shaking in the area with a radial extent of 100 km from the HPP site reaches the level VIII-IX of the MSK-64 scale (in the Tam Ky-Phuoc Son fault zone). At the HPP site, the maximum PGA value ranges between 0.1g and 0.13 g (VII-VIII levels in the MSK-64 scale). The PGA maps present both short - term and long - term forecasts of seismic hazard in Quang Nam province. Calculated shakings at the HPP’s site can be used for seismic safety evaluation and antiseismic design for the HPP’s facilities during its operational time. References Budnitz, R.J., Apostolakis G., Boore D. M., Cluff L. S., Coppersmith K. J., Cornell C. A., Morris P. A., 1997. Recommendation for Probabilistic Seismic Hazard Analysis: Guidance on Uncertainty and Use of Experts. NUREG/CR-6732, 1. Cornell, C.A., 1968. Engineering Seismic Risk Analysis, Bull. Seim. Soc. Am., 58, 1583-1606. Crowley, H., D. Monelli, M. Pagani, V. Silva, G. Weatherill, 2011. OpenQuake Book. The GEM Foundation, Pavia, Italy. Esteva, L., 1968. Bases para la formulacion de decisiones de diseno sismico. PhD thesis, Universidad Autonoma Nacional de Mexico. Gumbel, E. J., 1958. Statistics of Extremes, Columbia University Press. Nguyen Hong Phuong (Editor), 2013. Assessment of earthquake and tsunami hazards in the Ninh Thuan province for site approval of the NPPs”.  Final report of the 2013 National Scentific Research Project, Institute of Geophysics, Hanoi, 2013 (in Vietnamese). Nguyen Hong Phuong , Que Cong Bui, Xuyen Dinh Nguyen, 2012. Investigation of tsunami sources, capable of affecting the Vietnamese coast. Natural Hazards, 64(1), 311-327. DOI: 10.1007/s11069-012-0240-3, Nguyen Hong Phuong, 2004. Seismic Hazard Maps of Vietnam and the East Vietnam Sea. Journal of Earth’s Sciences, 26(2), 97-111, 2004 (in Vietnamese). Nguyen Hong Phuong, Bui Cong Que, Vu Ha Phuong and Pham The Truyen, 2014. Scenario-based Tsunami Hazard Assessment for the coast of Vietnam from the Manila Trench source. Physics of the Earth and Planetary Interiors. DOI: 10.1016/j.pepi.2014.07.003. Nguyen Hong Phuong, Pham The Truyen, 2015. Probabilistic Seismic Hazard Maps of Vietnam and the East Vietnam Sea. Journal of Marine Science and Technology, 15(1), 77-90. DOI: 10.15625/1859-3097/15/1/6083 (in Vietnamese). Nguyen Ngoc Thuy et al., 2003. Assessment of seismic hazard for the Tranh River hydropower plant No2. A pre-feasebility report, Institute of Geophysics, Hanoi, October 2003, 75 p. (in Vietnamese). Nguyen, L. M., et al, 2012. The first peak ground motion attenuation relationships for North of Vietnam, Journal of Asian Earth Sciences, doi: 10.1016/j.jseaes.2011.09.012. OYO corporation, 2013. Research, Detailed Review of Geological Condition, Geodynamics and Geological Activities in Song Tranh 2 Hydropower Area (Bac Tra My District, Quang Nam Province). Draft Final Report No.: 01/2013/SACQI-OYO,  101 pp. Pacific Earthquake Engineering Research Center, 2008. NGA model for average horizontal component of peak ground motion and response spectra. Earthquake Spectra, 24(1), Petersen Mark D., James Dewey, Stephan Hartzell, Charles Mueller, Stephan Harmsen, Arthur D. Frankel, Ken Rukstales, 2004. Probabilistic seismic hazard analysis for Sumatra, Indonesia and across the Southern Malaysian Peninsula. Tectonophysics, 390, 141-158. Toro, G. R., 2002. modification of the Toro et al. (1997) attenuation equations for large magnitudes and short distances. Risk Engineering Incl., June. Toro, G. R., Abrahamson, N. A., and Schneider, J. F., 1997. Engineering model of strong ground motions from earthquakes in the central and eastern United States. Seismological Research Letters, 68(1): 41-57. Tran Viet Hung and Kiyomiya, O., 2012. Ground motion attenuation relationship for shallow strike-slip earthquakes in northern Vietnam based on strong motion records from Japan, Vietnam and adjacent regions, Structural Eng./Earthquake Eng., JSCE, 29, 23-39. Vu Van Chinh (Editor), 2015. Study and detailed evaluation of the regional seismotectonic characteristics and their impact to the stability of the Tranh River hydropower plant No2 and Northern Tra My area, Quang Nam province. A Thematic report of the 2013 National Scentific Research Project ” Study of the seismotectonic impact to the stability of the Tranh River hydropower plant No2 in Northern Tra My area, Quang Nam province”, Institute of Geophysics, Hanoi, 2015 (in Vietnamese). Wieland M., 2010. Selecting seismic parameters for large dames - Guidelines. ICOLD Bulletin 72, 2010 Revision.